Tinjauan Konsep Mubadalah dan Tafsir Maqashidi dalam Merespon Isu Kekerasan Seksual - Abd. Basid; Syukron Jazila (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA, 2023)
Sexual violence often occurs to this day, and efforts to resolve and suppress the number of sexual violence through studies and research embodied in various topics continue to be carried out as a form of responsiveness to the issue of gender-based inequality of justice. This study aims to find out the resolution of issues around gender through the relationship between the concepts of mubadalah and maqashidi interpretation. The model of reading texts with mutuality (mubadalah), which is then compared with the maqashidi-based interpretation style as a promoter of benefit, the relationship between these two studies is considered to be able to respond to the issue of inequality of justice in the context of sexual violence. This study uses qualitative methods and library research. Based on this research, it can be concluded that interpreting maqashid al-syari'ah review as a philosophical basis which is then compared with the performance steps of the concept of interpretation mubadalah is to give birth to maqashid al-Qur'an, which puts forward mashalih lil anam (benefit to the all human beings) can rectify pragmatic hegemony regarding the issue of violence against women.